(untitled) (Revista Latino-Americana de Enfermagem, 2007)
Analysis of patient classification instruments available in the literature shows that many significant aspects related to the assistance to patients with wounds are not approached, evidencing the importance to elaborate criteria to assess these patients. This study proposes the development of new of areas of care to complement the Fugulin et al. instrument, validated by the Federal Nursing Council (COFEN). The construction of new areas to evaluate wounds was based on a bibliographic search on the operational models of the Patient Classification System (PCS), as well as on several instruments of wound classification. New areas of care were established, as follows: tissue impairment, number of dressing changes and time taken to their preparation. Values were also redefined indicating the patient's assistance category. The complementation of the Fugulin et al. instrument, proposed here, favors the application of this instrument in a more diversified group of patients since it adds a relevant assistance aspect, as the dressing issue.